We have $f=(x+i)^{10}+(x-i)^{10}$ and we need to prove that $f$ have all the roots in $\mathbb{R}$.

Here is all my steps:

  • Suppose that $z\in\mathbb{R}$ is a root of $f\Rightarrow (z+i)^{10}+(z-i)^{10}=0$

Therefore: $f(z)=\sum_{k=0}^{10}\left[\left(\dbinom{10}{k}\cdot z^{10-k}\cdot i^k\right)\left(1+(-1)^k\right)\right]=0$

I don't have ideea how can I prove that $f$ have all real roots

Suppose that $z=a+bi$ and we need to prove that $b=0$:

$$\Rightarrow f(z)=\sum_{k=0}^{10}\left(\dbinom{10}{k}\cdot a^{10-k}\cdot i^k\right) \left[(b+1)^k+(b-1)^k \right]=0$$

$$\Rightarrow \left[(b+1)^k+(b-1)^k \right]=0$$

$$\Rightarrow b+1=-b+1$$ $$\Rightarrow b=0$$

Therefore $f$ have all the roots in $\mathbb{R}$

  • Here is a photo with the proof of real axis, I don't know if is correct:

enter image description here


Let $a+ib$ be an imaginary root of $f$ , where , $a,b\in \mathbb R$. Then $$f(a+ib)=0$$

$$\implies (a+i(b+1))^{10}+(a+i(b-1))^{10}=0$$

Expand two binomial series , and separate real part and imaginary parts. Put them separately $0$. Then you obtain the value of $b$, which would be zero, if the problem is proper.

| cite | improve this answer | |
  • $\begingroup$ S.Panja from here I have to expand $(a+i(b+1))^{10}$ in binominal series? $\endgroup$ – Lucas Jun 5 '15 at 8:02
  • $\begingroup$ I cancel your downvote $\endgroup$ – Lucas Jun 5 '15 at 8:08
  • $\begingroup$ Panja I will edit with binominal series and I want to tell me if is correct $\endgroup$ – Lucas Jun 5 '15 at 8:09
  • $\begingroup$ Panja is correct ? $\endgroup$ – Lucas Jun 5 '15 at 8:32

$(x+i)^{10}+(x-i)^{10}=0$ immediately implies $|x+i|=|x-i|$, which is equivalent to $x \in \mathbb R$ (the real axis is the perpendicular bisector of the line from $i$ to $-i$).

| cite | improve this answer | |
  • $\begingroup$ can you give me a draw ? because I don't know to make it $\endgroup$ – Lucas Jun 5 '15 at 8:04
  • $\begingroup$ What exactly you do not know/understand about this proof? Be more precise. $\endgroup$ – MooS Jun 5 '15 at 8:07
  • $\begingroup$ MooS I can't understand your method, can you give some explanations ? $\endgroup$ – Lucas Jun 5 '15 at 8:11
  • 2
    $\begingroup$ @Lucas: |x+i| is the distance of $x$ from $-i$ and $|x-i|$ is the distance of $x$ from $i$. The locus of points that are equidistant from $-i$ and $i$ is the real axis. $\endgroup$ – robjohn Jun 5 '15 at 11:44
  • 1
    $\begingroup$ All roots satisfy $|x-i|=|x+i|$. So this works fine without further arguments. $\endgroup$ – MooS Jun 5 '15 at 18:41

$(x+i)^{10} = -(x-i)^{10} = i^{10}(x-i)^{10} = (i(x-i))^{10} \to \left(\dfrac{x+i}{ix+1}\right)^{10} = 1$. Can you continue??

| cite | improve this answer | |
  • $\begingroup$ notaloner I can't understand how you obtain $\left(\frac{x+i}{1+ix}\right)^{10}$ and I can't continue $\endgroup$ – Lucas Jun 5 '15 at 8:23
  • $\begingroup$ first, $i(x-i) = ix - i^2 = ix+1$, and secondly use $a^{10} = b^{10} \iff \left(\dfrac{a}{b}\right)^{10} = 1$ $\endgroup$ – DeepSea Jun 5 '15 at 8:25
  • $\begingroup$ NotALoner if I continue your method I obtain something like this $\frac{(x+i)(ix-1)}{-x^2-1}=1\Rightarrow x^2(-1-i)+2x+i-1=0$ and I suppose we need to put condition that: $4-4(-1-i)(i-1)\geq 0$ isn't it ? $\endgroup$ – Lucas Jun 5 '15 at 8:47
  • $\begingroup$ after I obtain: $-4\geq 0$ which is a contradiction $\endgroup$ – Lucas Jun 5 '15 at 8:51
  • $\begingroup$ can you explain what you want by this method ? $\endgroup$ – Lucas Jun 5 '15 at 8:57

Here is another way of showing that all solution are real valued.

$(x+i)^{10}+(x-i)^{10}=0\implies\,\,\left(\frac{x+i}{x-i}\right)^{10}=e^{in\pi}\implies \frac{x+i}{x-i}=e^{in\pi/10} \implies x=\cot(n\pi/20)$

which are real-valued for all integer $n$.

To answer the question regarding the substitution $z=a+ib$ and subsequent analysis, if $(b+1)^k+(b-1)^k=0$, then this implies that $b=-i\cot (n\pi/2k)$ for all integer $n$ and $k=0, 1, 2, \cdots 10$.

But, since $b$ is presumed to be real valued, then this implies $b=0$ (i.e., only solutions with $n/k$ odd are valid).

However, this assumption (i.e., $(b+1)^k+(b-1)^k=0$) is not the basis for a proof that $b=0$.

| cite | improve this answer | |
  • $\begingroup$ @Lucas I'm not sure that this is what you were looking for, but hope that it helps. $\endgroup$ – Mark Viola Jun 5 '15 at 17:35
  • $\begingroup$ Dr.Mv why $(x+i)^{10}+(x-i)^{10}$ leds to absolute value: $|x+i|=|x-i|$ ? $\endgroup$ – Lucas Jun 5 '15 at 17:44
  • $\begingroup$ @Lucas Well, that result was not used here. But you recall that $|z|^n=|z^n|$. So, letting $z=\frac{x+i}{x-i}$, we have $|z^{10}|=|-1| \implies |z|^{10}=1\implies |z|=1$ is one root. But there are other roots. $\endgroup$ – Mark Viola Jun 5 '15 at 17:49
  • $\begingroup$ Dr.Mv how can I continue my solution with binominal series ? $\endgroup$ – Lucas Jun 5 '15 at 17:52

You can transform the equation in


Then, solving for $x$ and using $|z|=1$, $$x=i\frac{z+1}{z-1}=i\frac{(z+1)(\overline z-1)}{(z-1)(\overline z-1)}=i\frac{|z|^2-1+\overline z-z}{|z|^2+1-z-\overline z}=\frac{2\Im z}{2-2\Re z}.$$

| cite | improve this answer | |
  • $\begingroup$ my binominal series is correct ? $\endgroup$ – Lucas Jun 5 '15 at 9:32
  • $\begingroup$ Yes but the conclusion you draw from it is not. $\endgroup$ – Yves Daoust Jun 5 '15 at 9:35
  • $\begingroup$ and how can I continue at final ? $\endgroup$ – Lucas Jun 5 '15 at 9:40
  • $\begingroup$ Leads you to a system of two polynomial equations in two unknowns. $\endgroup$ – Yves Daoust Jun 5 '15 at 9:48
  • $\begingroup$ and which is two polynomial equations ? $\endgroup$ – Lucas Jun 5 '15 at 9:50


$$(x+i)^{10}+(x-i)^{10}=0 \Rightarrow (x+i)^{10}=-(x-i)^{10} \Rightarrow (\frac{x+i}{x-i})^{10}=-1 \\ \Rightarrow \left (\frac{a+(b+1)i}{a+(b-1)i}\right )^{10}=i^{10} \Rightarrow \frac{a+(b+1)i}{a+(b-1)i}=i \\ \Rightarrow \frac{(a+(b+1)i)(a-(b-1)i)}{(a+(b-1)i)(a-(b-1)i)}=i \Rightarrow \frac{a^2-a(b-1)i+a(b+1)i+(b^2-1)}{a^2+(b-1)^2}=i \Rightarrow \frac{(a^2+(b^2-1))+2ai}{a^2+(b-1)^2}=i$$

That means that $$\frac{a^2+(b^2-1)}{a^2+(b-1)^2}=0 \text{ and } \frac{2a}{a^2+(b-1)^2}=1$$

$$\frac{a^2+(b^2-1)}{a^2+(b-1)^2}=0 \Rightarrow a^2+b^2-1=0 \Rightarrow b^2=1-a^2$$

$$\frac{2a}{a^2+(b-1)^2}=1 \Rightarrow 2a=a^2+(b-1)^2 \Rightarrow 2a=a^2+b^2-2b+1 $$

Solving for $a$ and $b$ we get the following solutions:

$a=0, b=1$ and $a=1, b=0$

We reject $(a, b)=(0, 1)$ because then the denominator would be $0$.

So, the solution is $(a, b)=(1, 0)$.

That means that $x=1 \in \mathbb{R}$.


Do the same for the case $\left (\frac{a+(b+1)i}{a+(b-1)i}\right )^{10}=i^{10} \Rightarrow \frac{a+(b+1)i}{a+(b-1)i}=-i$

| cite | improve this answer | |
  • $\begingroup$ Mary Star what's wrong in my binominal series ? I can't see the real part in my solution $\endgroup$ – Lucas Jun 5 '15 at 11:47
  • $\begingroup$ You can't go from $x^{10}=y^{10}$ to $x=y$ as you do in the second line of your proof here. $\endgroup$ – Steven Stadnicki Jun 5 '15 at 18:42
  • $\begingroup$ why it can't do it ? $\endgroup$ – Lucas Jun 6 '15 at 6:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.